KONTRIBUSI TEORI INTERPRETASI PSIKOANALISIS DAN HERMENEUTIK TERHADAP PROSES ANALISIS/PENGKAJIAN FILM - Harifa Ali Albar Siregar (Fakultas Seni Rupa dan Desain ITB, 2011)
Film has a role position in society nowadays. Not only as an entertainment, education or communication purposes, film could also reflects all the aspects in the real live of humankind. This paper is an attempt to analyze film using the psychoanalysis interpretation method with hermeneutic approach. The method will assume the dream and dreamers position in watching film. These steps discovered the connection between past experiences with the recent works as a result of past identification. The combination of film theories and the psychoanalysis intrepretation method will deepen our understanding to the existence of film. Keywords: Film, psychoanalysis interpretation, hermeneutic.